2018
DOI: 10.1111/rec.12840
|View full text |Cite
|
Sign up to set email alerts
|

Selection for genetics‐based architecture traits in a native cottonwood negatively affects invasive tamarisk in a restoration field trial

Abstract: Climate change and competition from invasive species remain two important challenges in restoration. We examined the hypothesis that non‐native tamarisk (Tamarix spp.) reestablishment after aboveground removal is affected by genetics‐based architecture of native Fremont cottonwood (Populus fremontii) used in restoration. As cottonwood architecture (height, canopy width, number of stems, and trunk diameter) is, in part, determined by genetics, we predicted that trees from different provenances would exhibit dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…For example, recent common garden experiments have shown significant differences in canopy architecture for P. fremontii from provenance regions with 3-5 C differences in mean annual maximum temperature (Mahoney, Mike, Parker, Lassiter, & Whitham, 2019). type, and measuring LAI in situ was infeasible for this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, recent common garden experiments have shown significant differences in canopy architecture for P. fremontii from provenance regions with 3-5 C differences in mean annual maximum temperature (Mahoney, Mike, Parker, Lassiter, & Whitham, 2019). type, and measuring LAI in situ was infeasible for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Improved estimation of LAI from remotely sensed data is an important topic for future research. For example, recent common garden experiments have shown significant differences in canopy architecture for P. fremontii from provenance regions with 3–5°C differences in mean annual maximum temperature (Mahoney, Mike, Parker, Lassiter, & Whitham, 2019). Transposing use of LAI‐NDVI calibration relationships from the Lower Colorado (with MAMT closer to 30°C) to the cooler San Pedro region (MAMT about 25°C) was necessary for this study because the Lower Colorado relationships were the closest available for this vegetation type, and measuring LAI in situ was infeasible for this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, if a tree loses its leaves during the dry season, this is the predictor of lower PAR interception rather than its crown traits. In addition, light interception by crowns may not be completely predictable by models since tree architecture is determined according to genetics (Benomar et al ; Mahoney et al ) as well as environmental conditions and competition with other species (Uriarte et al ; Del Río et al ; Fichtner et al ; Van de Peer et al ).…”
Section: Discussionmentioning
confidence: 99%
“…We also assessed the performance of each tree by measuring tree diameter and classified each tree as either shrub-like or tree-like. A previous study at Chevelon Garden has shown that poorly performing trees were shorter, had smaller trunks, and had more stems (i.e., "shrub-like") than better performing trees (Mahoney et al 2018). The architecture of each tree was classified as either "shrub" or "tree" with shrubs having more than two trunks.…”
Section: Sampling and Data Collectionmentioning
confidence: 99%